2010
DOI: 10.1517/14712598.2010.534080
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of toll-like receptor function has therapeutic potential in autoimmune disease

Abstract: As initiators of immune responses, TLRs have previously been targeted to increase the immune response with some success. However, targeting TLRs to attenuate immune responses for the treatment of chronic inflammatory diseases will require further evidence of the mechanisms of TLR involvement in the pathophysiology and a better understanding of the potential effects of modulating TLR physiology over a sustained period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 158 publications
0
19
0
Order By: Relevance
“…Activation of TLRs has been linked to the pathogenesis of various autoimmune inflammatory diseases including rheumatoid arthritis, systemic lupus erythematosus, and inflammatory bowel disease (Clanchy and Sacre, 2010). Among the TLR family members, TLR4 has been recognized as being important for islet cell inflammation and eventually β cell loss in the course of T1D development.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of TLRs has been linked to the pathogenesis of various autoimmune inflammatory diseases including rheumatoid arthritis, systemic lupus erythematosus, and inflammatory bowel disease (Clanchy and Sacre, 2010). Among the TLR family members, TLR4 has been recognized as being important for islet cell inflammation and eventually β cell loss in the course of T1D development.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that the upstream mechanisms that generate inflammation are still functional and most likely unaffected by these treatments. Many studies from both murine and human models have suggested a role for a family of innate immune receptors, the Toll-like receptors (TLRs) in RA pathogenesis [5]. …”
Section: Introductionmentioning
confidence: 99%
“…The increasing recognition that viruses, and in particular EBV, can be etiological factors driving the development of MS or other autoimmune diseases in genetically susceptible individuals further strengthens the potential of administering anti-viral therapies to people affected by these disorders [12]. In line with this view, the increased TLR7 gene expression observed upon IFN-β might be part of a specific antiviral program induced by this cytokine that could counteract dysregulated responses to viral infection in MS patients.Targeting TLRs and modulating their functions are increasingly recognized as potential therapeutics for different autoimmune diseases, including rheumatoid arthritis, systemic lupus erythematosus, and MS [15,53]. Indeed, a common trait of most autoimmune disorders is a chronic inflammation occurring at specific sites within the body or as a systemic complication suggested to be sustained also by TLR activation.…”
mentioning
confidence: 99%